2001
DOI: 10.1191/096120301680416977
|View full text |Cite
|
Sign up to set email alerts
|

A possible role of apoptosis for regulating autoreactive responses in systemic lupus erythematosus

Abstract: It has been reported that apoptotic cells are increased in the peripheral blood from patients with systemic lupus erythematosus (SLE), where dysfunctions of T helper 1 (Th1) cells are known. In order to study whether apoptosis of Th1 cells is associated with the pathogenesis of SLE, early apoptotic cells in various T-cell subsets were detected using fluorescence-labeled annexin V (AnV). AnV binding was most frequently observed in CD4+CCR5+ T cells, and AnV binding rate (%) in this subset was higher in SLE than… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2003
2003
2011
2011

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 21 publications
0
15
0
Order By: Relevance
“…Similarly to various systemic autoimmune diseases, in which altered apoptosis capability of PBMCs is characteristic and may contribute to the maintenance of the autoimmune processes (Bijl et al, 2001;Funauchi et al, 2001;Papo et al, 1998;Stummvoll et al, 2000;Zeher et al, 1999), our findings revealed the presence of activated peripheral blood T lymphocytes with impaired apoptosis, resulting in long-lived T cells peripherally in RA. This may contribute to the recruitment of these cells to the site of tissue damage and the perpetuation of the autoimmune inflammatory process.…”
Section: Szodoray Et Almentioning
confidence: 85%
See 1 more Smart Citation
“…Similarly to various systemic autoimmune diseases, in which altered apoptosis capability of PBMCs is characteristic and may contribute to the maintenance of the autoimmune processes (Bijl et al, 2001;Funauchi et al, 2001;Papo et al, 1998;Stummvoll et al, 2000;Zeher et al, 1999), our findings revealed the presence of activated peripheral blood T lymphocytes with impaired apoptosis, resulting in long-lived T cells peripherally in RA. This may contribute to the recruitment of these cells to the site of tissue damage and the perpetuation of the autoimmune inflammatory process.…”
Section: Szodoray Et Almentioning
confidence: 85%
“…Because PBMCs play an important role in the pathogenesis of various systemic autoimmune diseases, such as systemic lupus erythematosus (Bijl et al, 2001;Funauchi et al, 2001;Papo et al, 1998), Sjögren's syndrome (Zeher et al, 1999), and systemic sclerosis, (Stummvoll et al, 2000), we further investigated this phenomenon in RA.…”
mentioning
confidence: 99%
“…Several intracellular mechanisms by which monocyte/macrophage/T-helper cell apoptosis rates are elevated in SLE have been proposed [147][148][149][150][151][152]. These include, persistent mitochondrial hyperpolarization via elevated mitochondrial transmembrane potential (i.e.δPsim) and ATP depletion [149], increased hypermutated memory B cells [147,150], elevated COX-2 production [151] and 7, 8 dihydroneopterin-resistance [152].…”
Section: Psoriatic Arthritismentioning
confidence: 97%
“…These include, persistent mitochondrial hyperpolarization via elevated mitochondrial transmembrane potential (i.e.δPsim) and ATP depletion [149], increased hypermutated memory B cells [147,150], elevated COX-2 production [151] and 7, 8 dihydroneopterin-resistance [152].…”
Section: Psoriatic Arthritismentioning
confidence: 99%
“…Defects in inducing apoptosis could lead to the persistence of autoreactive T-or B-cells. On the other hand, apoptosis generates altered self-antigens which can stimulate an autoimmune response in sensitive persons [19] .…”
Section: Discussionmentioning
confidence: 99%